Reproductive endocrinologist and infertility specialists' knowledge, skills, behaviors, and attitudes regarding the care for transgender and gender-diverse individuals - Pip Lipkin, M.D; Brent Monseur, M.D., Sc.M; Jonathan Mayo, M.P.H; Molly Moravek, M.D; Leena Nahata, M.D; Paula Amato, M.D; Ruben Alvero, M.D; Juno Obedin-Maliver, M.D., M.P.H., M.A.S (Elsevier, 2023)
Objective: To investigate associations between reproductive endocrinology and infertility (REI) providers' prior training and current knowledge, skills, attitudes, and behaviors regarding fertility preservation and family building for transgender and gender-diverse (T/GD) patients. Design: The survey was distributed to members of the Society for Reproductive Endocrinology and Infertility, the REI-physician-focused professional body within the American Society for Reproductive Medicine, with additional participants recruited through snowball sampling. Results: Participants (n = 206) reported on training in T/GD care; 51% endorsed prior training. Most participants (93%) believed T/GD individuals were as fit for parenthood as cisgender individuals. Prior training was associated with an increased likelihood of offering T/GD health resources and more frequent consultations with specialist colleagues.Common barriers to providing care indicated by respondents included cost, delays in gender-affirming care, and lack of knowledge of the potential impact of hormonal interventions. Common facilitators included education and training, prior experience, and affordability of services. Conclusions: Most REI providers believed T/GD individuals are fit for parenthood and agreed that prior training facilitates care for T/GD patients. The lack of provider knowledge emerged as a barrier to care. Although training helped facilitate some components of care, systemic barriers such as the cost and variability of patient population characteristics/experiences are important considerations when serving T/GD individuals.